(untitled) (Международный научный журнал «Инженер», 2026)
The purpose of this article to present a method of traffic management in terms of traffic safety and environmental safety in the city due to improving the mode of operation of intersections, changing its geometry. Information about the increase in the number of cars in Uzbekistan and their contribution to environmental pollution has been reflected. The results of the research conducted in the city of Karshi on the improvement of transport management are presented. In particular, it has been shown that the service level of the intersection (LOS) has improved due to the improvement of the operation mode of the intersection of Mustaqillik and Nasaf streets and the change of the geometry of the intersection I.Karimov and A.Temur streets. Determination of passenger flow in public transport using the PASSIM program and data on the intensity of vehicles in the city are presented. In order to find out the opinion of the population of Karshi about public transport, a social survey has been conducted among the population. The survey covered 1% of the total population of the city. The survey revealed that the number of bicycle users is increasing. Pedestrians also make up the majority of the population.